Heavy Metals in Commonly Consumed Root and Leafy Vegetables in Dhaka City, Bangladesh, and Assessment of Associated Public Health Risks - Romana Sultana; Rahamat Ullah Tanvir; Kazi Albab Hussain; Afrose Sultana Chamon; Md. Nadiruzzaman Mondol (Environmental Systems Research, 2022)
Abstract Background Excess accumulation of heavy metals in frequently consumed food (e.g., vegetables, fruits) is a serious threat to human health. The concentration of heavy metals in four root vegetables and five leafy vegetables collected from the Kawran Bazar fresh vegetable market of Dhaka, Bangladesh, were analyzed. Average daily intake (ADI), hazard quotient (HQ), and hazard index (HI) were also estimated to assess the human health risks posed by the intake of heavy metals from the consumption of the studied vegetables. Apparent differences in the concentration of heavy metals present in different vegetables were observed. Results The presence and degree of contamination was assessed for chromium (Cr), cadmium (Cd), lead (Pb), nickel (Ni), copper (Cu), zinc (Zn), iron (Fe), and manganese (Mn). Concentrations of Cr, Cd, Ni, and Cu exceeded the maximum permissible limit (MPL) in some root vegetables. Cr, Cd, Pb, Ni, Cu, Zn, and Fe concentration were higher in most studied leafy vegetables. ADI was found to be lower than the maximum permitted tolerable daily intake in most cases except Cr (0.202 mg/person day) and Fe (19.681 mg/person day) for the consumption of turnip and mint, respectively. Hazard quotient of Cr for turnip (1.121) and Zn for spinach (1.104), as well as the hazard indices of turnip (1.541), mustard (1.663), spinach (2.113), coriander (1.925), and mint (2.834), exceeded unit value, signifying potential health hazard from the dietary intake of the studied vegetables. Conclusions Higher concentrations of heavy metals were found in leafy vegetables compared to the root vegetables. Hence, the consumption of leafy vegetables has higher potential health risks than root vegetables. This study suggests that regular monitoring of heavy metals in vegetables is essential to prevent health risks associated with consuming heavy metal contaminated vegetables.